Physical size matters in the domestic dog's (Canis lupus familiaris) ability to use human pointing cues - Helton, William S.; Helton, Nicole D. (Behavioural Processes, 2010)
Researchers have reported differences between breeds of dogs in their ability to utilize human gestures (Wobber et al., 2009). These reports could either be the result of underlying differences in inherent communication abilities or differences in physical capacities amongst breeds. One physical difference between breeds which may make a difference in using visual cues is relative size. Larger dogs should, all other things being equal, have greater inter-ocular distances and this may improve their visual abilities for some tasks. This hypothesis was tested in the present study by comparing the performance of larger (> 22.7. kg) and smaller ( < 22.7. kg) dogs on a pointing choice task. Larger dogs did perform better on this task than smaller dogs (P= .03). Researchers need to be careful when making comparisons between breeds to first consider physical differences before assuming any inherent cognitive differences. Â© 2010 Elsevier B.V.